Deleuze's Concept of Quasi-cause. Issue 2 (May 2017) - Roffe, Jon
Abstract : The concept of quasi-cause is a relatively marginal one in the work of Gilles Deleuze, appearing briefly in The Logic of Sense and then Anti-Oedipus three years later. In part because of this marginality – the meagre degree to which it is integrated into the respective metaphysical system of the two works – it provides us with a useful vantage point from which to examine these systems themselves. In particular, a careful exposition of the two forms that the concept of the quasi-cause takes provides us with an aperture on the shifting role of the concepts of the virtual and the intensive in Deleuze's ongoing project. In this paper, I will argue that, through this aperture, it is possible to see the displacement of the virtual in favour of the intensive. In turn, we can characterise Anti-Oedipus as the birth of a fully actualist Deleuzian metaphysics.